Boric acid in germination of pollen grains and fruit set of peach cultivars in subtropical region (Revista Ciência Agronômica, 2017)
The pollination and fertilization process directly affects the crop yield of peach. Previous studies have shownthat some cultivars lack consistent cropping (yield variation) in subtropical regions. The application of boric acid at floweringcan minimize this problem. This study quantified the germination of pollen grains and fruit set on 18 cultivars of peach in asubtropical region when treated with boric acid at bud. The initial spray treatments were three concentrations of boric acid(400 mgL-1, 800 mgL-1 and 1,200 mgL-1) plus a control treatment of water. Treatments were sprayed on the shoots when theflower buds were flower bud swelling on early maturing cultivars Aurora 2 and Doçura 2. There is a cultivar differencewhere ‘Aurora 2’ had a negative effect from the application of boric acid on the percentage of germinated pollen grains andfruit set. ‘Doçura 2’ has a positive results at the concentration of 400 mgL-1 of boric acid. In a follow-up experiment with 18cultivars, using only the water control and 400 mgL-1 boric acid treatment, boron increases pollen grain germination and fruitset for some cultivars. The increase in germination and fruit set varies significantly among the cultivars. The concentrationof 400 mgL-1 of boric acid increases pollen germination and fruit set, but not in all cultivars.